2004
DOI: 10.1023/b:qure.0000037489.41344.b2
|View full text |Cite
|
Sign up to set email alerts
|

Health-related quality of life of children and adolescents with chronic illness – a two year prospective study

Abstract: The aim of this study was to compare the self-reported health-related quality of life (HRQL) of children and adolescents with diabetes, asthma or cystic fibrosis (CF) with the HRQL of a large community sample, to assess the extent to which the HRQL of the children and adolescents with chronic illness changes over time, and to examine the consistency of changes in different HRQL domains. One hundred and twenty three young people aged 10-16 years with asthma, diabetes, or CF were recruited from specialist paedia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
77
2
6

Year Published

2005
2005
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 115 publications
(95 citation statements)
references
References 6 publications
8
77
2
6
Order By: Relevance
“…The CHQ was not designed to serve as a measure to monitor change in HRQL (Landgraf et al 1996), but it has been suggested (Boyd and Hays 2001) and used (Perwien et al 2004) as an outcome measure in clinical trials. In other chronic disease states, the CHQ has demonstrated changes over time in some domains (Perwien et al 2004, Sawyer et al 2004, including improvement of Role -Physical. Poor sensitivity to change and poor face validity of the CHQ in CP have been cited as reasons to avoid or supplement the CHQ in clinical effectiveness research in CP (Bjornson and McLaughlin 2001).…”
Section: Discussionmentioning
confidence: 99%
“…The CHQ was not designed to serve as a measure to monitor change in HRQL (Landgraf et al 1996), but it has been suggested (Boyd and Hays 2001) and used (Perwien et al 2004) as an outcome measure in clinical trials. In other chronic disease states, the CHQ has demonstrated changes over time in some domains (Perwien et al 2004, Sawyer et al 2004, including improvement of Role -Physical. Poor sensitivity to change and poor face validity of the CHQ in CP have been cited as reasons to avoid or supplement the CHQ in clinical effectiveness research in CP (Bjornson and McLaughlin 2001).…”
Section: Discussionmentioning
confidence: 99%
“…1 Assessment of health-related QOL (HRQOL) of healthy children, as well as children with cancer, asthma, cystic fibrosis, chronic headache, arthritis and obesity has been reported to be a useful tool to characterize the global burden of the disease. 2 Obesity is increasing worldwide, reaching epidemic proportions. 3 Among children and adolescents, the prevalence of obesity is estimated to be about 20-25%.…”
Section: Introductionmentioning
confidence: 99%
“…[1]. HRQoL measures have commonly been used by physicians and psychologists to assess the effects of chronic illness in children and adolescents, and the extent to which an illness and its treatment can interfere with the their every day life [2][3]. However, recently this has been extended to the study and treatment of healthy children [4].…”
Section: Biological Maturation As a Confounding Factor In Relations Bmentioning
confidence: 99%